2014
DOI: 10.1136/bcr-2013-202236
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral retinitis pigmentosa: 30 years follow-up

Abstract: This case report depicts the clinical course of a female patient with unilateral retinitis pigmentosa (RP), who presented first in 1984 at the age of 43 years. At the beginning, there were cells in the vitreous leading to the diagnosis of uveitis with vasculitis. Within 30 years, the complete clinical manifestation of RP developed with bone spicule-shaped pigment deposits, pale optic disc, narrowed arterioles, cystoid macular oedema, posterior subcapsular cataract, concentric narrowing of the visual field and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 18 publications
0
18
0
7
Order By: Relevance
“… 18 Additionally, the identification and characterization of modifier genes, which themselves do not cause disease but “modify” the disease severity caused by other disease causing mutations is in its infancy, but has great potential for identifying new targets and approaches for treatment. Lastly, it may be worthwhile to evaluate patients with unilateral disease for somatic mutations 19 , 20 or other potential causes of retinal degeneration such as posterior uveitis, 21 acute zonal occult outer retinopathy, 22 or medication toxicity. 23 , 24 …”
Section: Recent Advances In Ird Researchmentioning
confidence: 99%
“… 18 Additionally, the identification and characterization of modifier genes, which themselves do not cause disease but “modify” the disease severity caused by other disease causing mutations is in its infancy, but has great potential for identifying new targets and approaches for treatment. Lastly, it may be worthwhile to evaluate patients with unilateral disease for somatic mutations 19 , 20 or other potential causes of retinal degeneration such as posterior uveitis, 21 acute zonal occult outer retinopathy, 22 or medication toxicity. 23 , 24 …”
Section: Recent Advances In Ird Researchmentioning
confidence: 99%
“…Uniocular pigmentary retinopathy is usually caused by either inflammation or trauma. Unilateral retinitis pigmentosa (RP) has long been proposed (Dreisler, 1948) and case reports exist in the literature (Farrell, 2009;Joseph, 1951;Kolb and Galloway, 1964;Mehra, 1962;Spadea et al, 1998;Thakur and Puri, 2010;Weller et al, 2014). Indeed, the prevalence of unilateral disease has been reported to vary between 0.02 and 5% depending on the population studied (Gauvin et al, 2016) but its existence has been a controversial one.…”
Section: Hereditary Retinal Diseasementioning
confidence: 99%
“…Farrell, et al [12], had two patients who were followed for 8 years and 14 years, respectively, and in both cases the unaffected eye had no signs of RP. Weller, et al [5], had one patient who showed no changes in the unaffected eye over a time span of 30 years. However, Gauvin and colleagues [33], had a patient present with unilateral retinitis pigmentosa who was seen eight separate times over thirty years during which bilateral retinitis pigmentosa developed.…”
Section: Prognosismentioning
confidence: 99%
“…There are few reports of unilateral retinitis pigmentosa in the literature, and some have complicating factors or represent extremely asymmetric retinitis pigmentosa [1,[5][6][7][8][9][10][11]. In retrospective reviews of those with retinitis pigmentosa, between 0.002 and 5% of the study populations had unilateral retinitis pigmentosa [1,3,12].…”
Section: Introductionmentioning
confidence: 99%